Experimental thrombocytopenia does not affect acute kidney injury 24 hours after renal ischemia reperfusion in mice - Jansen, Marcel. P.B.; Huisman, Andras; Claessen, Nike; Florquin, Sandrine; Roelofs, Joris J.T.H. (Platelets (Edinburgh), 2020)
The pathophysiology of renal ischemia/reperfusion (I/R) injury is characterized by excessive activation of inflammation and coagulation processes followed by abnormal renal tissue repair, resulting in renal injury and function loss. Platelets are important actors in these processes, however to what extent platelets contribute to the pathophysiology of renal I/R injury still needs to be elucidated. In the current study, we treated wild-type mice with a platelet depleting antibody, which caused thrombocytopenia. We then investigated the role of platelets during the pathophysiology of renal I/R by subjecting control wild-type mice with normal platelet counts and thrombocytopenic wild-type mice to renal I/R injury. Our results showed that in the early phase of renal I/R injury, thrombocytopenia 24 hours after ischemia reperfusion does not influence renal injury, neutrophil infiltration and accumulation of inflammatory chemokines (e.g. keratinocyte chemoattractant, monocyte chemoattractant protein 1, tumor necrosis factor alpha). In the recovery and regeneration phase of I/R injury, respectively 5 and 10 days post-ischemia, thrombocytopenia did also not affect the accumulation of intra-renal neutrophils and macrophages, renal injury, and renal fibrosis. Together, these results imply that lowering platelet counts do not impact the pathogenesis of I/R injury in mice.